A New Antiplasmodial Compound from the Papuan Marine Sponge Xestospongia sp. - Amir M Suruwaky; Kadarusman Kadarusman; Dikdik Kurnia; Tati Herlina; Unang Supratman; Murtihapsari Murtihapsari (Syarif Hidayatullah State Islamic University, 2018)
A new antiplasmodial compound, 2-(3H-diazirine-3-yl)benzaldehyde (1), has been isolated from the Papuan marine sponge Xestospongia sp. The structure elucidation of compound 1 was determined by spectroscopic evidences including UV, IR, MS, 1D and 2D-NMR analysis. Compound 1 showed moderate antiplasmodial activity against Plasmodium falciparum with IC50 value of 1.08 x 10-6 mM. DOI:http://dx.doi.org/10.15408/jkv.v4i1.6735